Strategic Positioning for Knowledge-Based Industry Growth: Bridging Innovation and Competitiveness Gaps - Haitham Al Qahtani; Jayendira P. Sankar (Ital Publication, 2026)
This study examines the strategic positioning of knowledge-based industries (KBIs) of Bahrain to address the innovation and competitiveness gaps within the Gulf Cooperation Council (GCC) region. This study adopted Porter’s Diamond model to identify critical factors that enhance the attractiveness of Bahrain as a KBI hub, which include key strengths of Bahrain’s location-based advantage, regulatory efficiency, and human capital readiness. This study used a mixed-method approach that integrates both qualitative and quantitative analyses by utilizing secondary data sources from GCC comparative benchmarks, policy documents, and international databases. The findings highlight the significant strengths of Bahrain in business-friendly policy, financial ecosystem, and information and communication technology (ICT) infrastructure. This study also identifies strategic pathways to further build upon these strengths, including continued domestic market diversification, increased research and development (R&D) investment, and expanded venture capital availability, reinforcing Bahrain's promising growth trajectory. Recommendations for actionable policy are proposed to expand fintech and artificial intelligence (AI) ecosystems and foster university-industry linkages. Thus, this study advocates for enhanced cross-GCC cluster collaboration to support the Bahrain Vision 2030 by applying and extending the competitive framework to KBI and contributing research to theoretical discussions on knowledge-driven economies. Overall, this study offers practical strategies for industry stakeholders and policymakers to strengthen the innovation ecosystem of Bahrain.